Penerapan Model Pembelajaran Discovery Learning Untuk Meningkatkan Hasil Belajar Siswa Kelas XI IPA Al-Jazari SMA Negeri 2 Pangkep - Paida, Andi; Auliyah, Tazkiyah; Hasyim, Nurhasana (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
ABSTRACT This research is motivated by observational data which shows that the acquisition of student learning outcomes in Indonesian material is low. To respond to that, the researchers conducted classroom action research which aimed to improve student learning outcomes. The objectives to be achieved in this study include: (1) knowing the implementation of the discovery learning method in improving student learning outcomes, (2) knowing the increase in student learning outcomes with the discovery learning method for students. This research was conducted in class XI IPA JAZ SMA Negeri 2 Pangkep with a total of 28 students. This study measures all domains that exist in learning outcomes, namely: cognitive, affective, and psychomotor. The results showed an increase in each domain in each cycle. This can be seen from the increase in learning outcomes in cycles I and II. In cycle I, there were still 8 or 27. 59 percent of students who did not pass the KKM and 20 or 72.41 percent of students passed KKM 72 with an average student learning achievement of 77.39. It increased in cycle II, all students passed the KKM with an average score of 86.61. The uses discovery learning method students get direct learning experience so that students are active in the learning process so that learning is more interesting and can improve student learning outcomes. Keywords: learning outcomes, discovery learning method.